Polly's absolutely worst birthday ever - Thomas, Frances, 1943-; Gardner, Sally (New York : Delacorte Press, 2003)
On Polly's ninth birthday, she has chicken pox and her pet hamster dies. However, a rescheduled party and new pets make her feel much better.
Accelerated Reader AR
Keywords: Birthdays -- Fiction; Chicken pox -- Fiction; Cats -- Fiction; Pets -- Fiction; Humorous stories